Nonlinear absorption spectrum in perylene derivatives - Oliveira, S. L.; de Boni, L.; Corrêa, D. S.; Misoguti, L.; Zílio, S. C.; Mendonça, C. R.; Constantino, C. J.L. [UNESP]; Aroca, R. F. (My University, 2005)
Knowledge about nonlinear absorption spectra of materials used in photonic devices is of paramount importance in determining their optimum operation wavelengths. In this work, we have investigated the two-photon absorption (2PA) degenerate cross-section spectrum for perylene derivatives using the Z-scan technique with femtosecond laser pulses. All perylene derivatives studied present large 2PA cross-sections, only comparable to the best ones reported in the literature. The results achieved in the present investigation indicate perylene derivatives as promising materials for two-photon applications. © 2005 Optical Society of America.